PELAKSANAAN TUGAS CAMAT DALAM PEMBINAAN BADAN PERMUSYAWARATAN KEPENGHULUAN (BPK) DI KECAMATAN KUBU KABUPATEN ROKAN HILIR - ", Harmain; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The Kubu district Kabuapaten Rokan Hilir its still not good coaching that dilakaukan by the District Head of the Consultative Body Kepenghuluan Kubu Kubu Sub Rokan Hilir.The theory used in the Head Coaching Duties Consultative Body Kepenghuluan Rokan Hilir District of camp, john suprihartono 1998 in his book entitled ratings execution of work and employee development, Yoyakarta LP3C publisher. Mastery of tasks, ability to work together, Ability finish work on time, reports on the existence of proper work.The purpose of the study, to investigate the implementation of tasks in the Guidance Consultative camat Kepenghuluan (CPC) in the district of Kubu Rokan Hilir. To determine what factors memghambat camat execution of tasks in coaching Kepenghuluan Consultative Body (BPK) in the district of Kubu Rokan Hilir.The method used in this thesis is to use qualitative descriptive methodology.From the research that I did, that the execution of tasks in Development Consultative Body Head Kepenghuluan Kecamtan Kubu, when seen from the results of interviews with several sources and some of the data that complements it can be said to be less good. Thus it can be seen also one of the few data and as well as the results of interviews which have implementation tasks, however not been able to arrive at a satisfactory level. So that every performance yaang done in quality is not maximized for the benefit of society.Keywords: Development, Human Resources and Infrastructures